Dampak cyberbullying terhadap kemampuan kecerdasan emosional remaja dengan pendekatan prakiraan - Syafindra, Yaumil; Yoesgiantoro, Donny (Journal of National Paradigm-Based Resilience Strategy, 2024)
The use of social media has become an inseparable part of teenagers' daily lives. Apart from having a positive impact, the existence of social media also has an impact on the negative behavior of its users, one of which is cyberbullying. This research aims to identify forms of cyberbullying among teenage victims on social media, estimate the impact of cyberbullying on teenagers' emotional intelligence abilities, and how to mitigate it. This research uses qualitative data collection techniques, including literature studies and expert interviews. The analysis uses qualitative thematics to identify forms of cyberbullying among teenage victims on social media, then analyzes predictions based on expert opinion and experience. The research results showed that there were five cases of teenage victims of cyberbullying in the form of insults and harassment on social media. Estimated impacts of these two forms of cyberbullying include teenagers having difficulty understanding and managing their own and other people's emotions, difficulty building social relationships, lack of self-confidence, stress, depression, and failure in academic achievement at school. Teenagers need to have the ability to mitigate adverse impacts; namely, first, teenagers do not need to respond to the cyberbullying they experience. Second, teenagers need support from their families and the school environment. Teenagers need to build good communication with their parents and understand how to use social media through literacy and legal risks by teachers at school. The government plays a vital role in controlling social media content that leads to cyberbullying (taking down the perpetrator's account).